Административное право России: курс лекций / под ред. Н. Ю. Хаманевой - Хаманева Наталия Юрьевна (Проспект, 2008)
Экземпляры: Ч/з (20090401) / Инвентарный номер: 94127 / Цена: 283.58 / Авт.знак: А 31 / ГРНТИ: 10 / ББК: 67.401я73